URL Degeneration: A Warning to Scholarly Community - Niveditha, B.; Kumbar, Mallinath (Journal of Information and Knowledge, 2022)
The present study examines the degeneration of web citations in scholarly journals of Library and Information Science, and Communication and Media Studies. The journals were selected based on their high impact factor published between 2008 and 2017. A PHP script was used to crawl the Uniform Resource Locators collected from the references. A total of 8,767 articles were downloaded and 3,97,140 references were extracted. A total of 71,289 URLs were checked for their availability. Further, the characteristic features of URL like file extension, path depth, character length and the toplevel domain were determined. The findings indicated that more number of URLs in LIS journal articles decayed than in Communication and Media Studies journal articles. The majority of errors in both the disciplines were HTTP 404 error code (Not found error). The findings of the study imply that authors, publishers and editorial staff need to ensure the availability of web resources before citing them.